Pengembangan Aplikasi Pembuat Gesture Pada Samsung Gear VR Untuk Game Engine Unity - Dwi Rama Malawat; Muhammad Aminul Akbar; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Virtual Reality (VR) is a technology that provide a user to interact with virtual world simulated by computer. To maximize the user experience in VR, a VR system must be able to recognize natural movement such as gesture. That's why gesture recognition system is important. Mobile VR development gets a lot of attention because of the increase use of cellular devices. One of the mobile VR devices is Head-Mounted Display (HMD), which is a display monitor that attached to the head to display virtual environment. Gesture recognition system can be implemented on HMD with controller such as Samsung Gear VR. Developing VR applications that have gesture recognition capabilities can take a lot of time, currently there are libraries that provide the ability to create gesture recognition system but the libraries only support VR Headset devices with 6DOF, but Samsung Gear VR only have 3DOF. In this research we have develop Gesture Creator Application on Samsung Gear VR for Unity Game Engine, this tool help developer to create and define new gestures and implement it to their VR application. By giving gesture through the controller, this application can record and define the gestures. Functionality of this application has been tested with Blackbox Testing and the result are valid as expected of the system requirement. This application use artificial neural network algorithm to predict the result with 86.67% accuracy. The result of usability testing using System Usability Scale (SUS) method is 65, which means this application get grade D or Good and categorized as Acceptable.